Representation and Inclusion in School Councils in Mozambique - Taela, Kátia; López Franco, Erika; Alex, Shankland; Maivasse, Catija; Chilengue, Nárcya; Goodfry, Claudino (Institute of Development Studies, 2018)
This study was conducted as part of the Citizen Engagement Programme (Programa Cidadania e Participação (CEP)) in Mozambique – an empowerment and social accountability initiative to improve the quality of education and health services by increasing citizens’ influence on the management of schools and health units, the formulation of education and health policies, and the provision of education and health services. In education, CEP enabled citizen monitoring of services through the community scorecard (Cartão de Pontuação Comunitária (CPC)), focusing on the link between CPC action plans and the work plans of the co-management mechanism in schools – the school councils. CEP has also promoted the channelling of issues beyond the capacity and mandate of schools to higher levels of the national education system. This work identified a need to better understand the role of school councils as a link between the school and the community, and also in escalating important matters to higher levels of management in the education system, beyond that of school authorities. It was in this context that the Institute of Development Studies and the Centre for Learning and Capacity Building for Civil Society, both members of the CEP consortium, proposed to undertake a qualitative study on representation and inclusion in school councils. The primary aim of this study was to widen the knowledge base available to civil society and to government on the factors that contribute to good performance by school councils in building inclusivity and social accountability to improve the quality of education services.
978-1-78118-441-7
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; Important; L - english / inglês; M - ethnography / etnografia; access to services / acesso a serviços; citizenship & participation / cidadania e participação; civil society / sociedade civil; decentralization / descentralização; education / educação; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Education Service Delivery in Mozambique: A Second Round of the Service Delivery Indicators Survey - Bassi, Marina; Medina, Octavio; Nhampossa, Lúcia (World Bank, 2018)
This report presents the findings of the second round of the Service Delivery Indicators Survey (SDI) in Mozambique. The SDI analyses the performance of the education sector by assessing the quality of service delivery at the school level. SDI has been implemented in nine countries in Africa, including Mozambique in 2014.5 The study includes a set of indicators that measures teachers and principals’ ability and effort, as well as the availability of key inputs and resources that contribute to the functioning of a school. These metrics enable education authorities and schools to identify gaps and track progress over time (and across countries). The analysis is centered around three main questions: what do providers know? (teacher ability), what do providers do? (teacher effort), and what do providers have to work with? (input availability).
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - indicators / indicadores; Northern PEA; education / educação